1992
DOI: 10.1088/0963-0252/1/3/011
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic scheme of the non-equilibrium discharge in nitrogen-oxygen mixtures

Abstract: A kinetic scheme for non-equilibrium discharge in nitrogen-oxygen mixtures is developed, which almost wholly describes chemical transformations of particles in t h e cold (200 K g T < 500 K) vibrationally unexcited gas. The kinetic scheme includes processes of excitation of electronic states, destruction and ionization of heavy panicles by electron impact, associative ionization, electron attachment and detachment, electron-ion and ion-ion recombination, chemical transformations of neutral panicles (in ground … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
1,040
1
7

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,540 publications
(1,071 citation statements)
references
References 32 publications
23
1,040
1
7
Order By: Relevance
“…The present quasi-zero-dimensional model is sufficiently accurate to predict the amplitude of pressure perturbations and compression waves generated by high specific energy loading, nanosecond pulse discharges in air. Although the present model can be easily extended to incorporate vibrationally enhanced chemical reactions postulated in previous work, such as N 2 [45,46], in this work the effect of these reactions on plasma chemistry of air and fuel-air mixtures is not taken into account, since evidence of these reactions in nanosecond pulse discharges remains limited and indirect. In particular, our previous study of the mechanism of NO formation in nanosecond pulse discharges [11,12] demonstrated the effect of N 2 (X 1 Σ, v) reactions at these conditions to be negligible compared with reactions of electronically excited N * 2 molecules.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present quasi-zero-dimensional model is sufficiently accurate to predict the amplitude of pressure perturbations and compression waves generated by high specific energy loading, nanosecond pulse discharges in air. Although the present model can be easily extended to incorporate vibrationally enhanced chemical reactions postulated in previous work, such as N 2 [45,46], in this work the effect of these reactions on plasma chemistry of air and fuel-air mixtures is not taken into account, since evidence of these reactions in nanosecond pulse discharges remains limited and indirect. In particular, our previous study of the mechanism of NO formation in nanosecond pulse discharges [11,12] demonstrated the effect of N 2 (X 1 Σ, v) reactions at these conditions to be negligible compared with reactions of electronically excited N * 2 molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Although much is still left to be learned on rates and product distributions of reactions of hydrogen and hydrocarbon molecules with plasma electrons and excited molecules and atoms, the amount of experimental data accumulated in nanosecond pulse discharges in air, hydrogen-air and small hydrocarbon-air mixtures, as well as significant depth of knowledge in kinetic modelling of non-equilibrium air plasmas (e.g. [2]), are making possible development of a kinetic mechanism of low-temperature plasmainduced combustion, with reasonable predictive capability. This mechanism needs to be validated using experimental data, such as temperature, vibrational levels populations, number densities of excited electronic states of atoms and molecules, radical species number densities, ignition temperature and ignition delay time taken in fuel-air mixtures excited by non-equilibrium plasmas, at well characterized conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[33] That affect the excited species N 2 (a′ 1 S u − ) are the radiative transition (Ogawa-Tanaka-Wilkinson-Mulliken band system, a′ 1 S u − −X 1 S g + ) [Lofthus and Krupenie, 1977], the production of two O atoms [Kossyi et al, 1992], the quenching processes with N 2 and O 2 [Umemoto et al, 2003], and the reactions that produce N, O, and N 4 + [Sentman et al, 2008, and references therein]. The radiative lifetime of a′ 1 S u − −X 1 S g + is 0.5 s, since its Einstein coefficient is 2 s −1 .…”
Section: Discussionmentioning
confidence: 99%
“…This can be linked with the kinetics of air plasma chemistry where excited nitrogen species are favoured over oxygen species for extended time scales [40]. This type of exclusive competitive reaction mode has also been suggested for photo-induced degradation of diuron (herbicide) in aqueous solution by nitrites and nitrates with photolysis of water (which yields OH radicals) [41].…”
Section: Figure 6 Proposed Reaction Products For Cyprodinil (Based Onmentioning
confidence: 94%